2016
DOI: 10.1001/jamaoncol.2016.0429
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease After Aromatase Inhibitor Use

Abstract: The risk of the most serious cardiovascular events (cardiac ischemia or stroke) was not elevated in AI-only users compared with tamoxifen users. The finding that other CVD events combined were greater in AI users requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 28 publications
1
73
3
1
Order By: Relevance
“…Many anticancer drugs used to treat patients with advanced/metastatic breast cancer have been associated with early or delayed cardiac side effects, from left ventricular (LV) dysfunction to overt heart failure, arrhythmias, myocardial ischemia, valvular disease, thromboembolic disease, pulmonary hypertension, arterial hypertension, and pericarditis . Here, we explore the cardiac effects observed with radiotherapy, chemotherapy, endocrine therapy, and other approved targeted therapies for metastatic breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Many anticancer drugs used to treat patients with advanced/metastatic breast cancer have been associated with early or delayed cardiac side effects, from left ventricular (LV) dysfunction to overt heart failure, arrhythmias, myocardial ischemia, valvular disease, thromboembolic disease, pulmonary hypertension, arterial hypertension, and pericarditis . Here, we explore the cardiac effects observed with radiotherapy, chemotherapy, endocrine therapy, and other approved targeted therapies for metastatic breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no evidence that menopausal status was a confounder of the relationship between aromatase inhibitors and HF (data not shown). A number of studies have suggested that aromatase inhibitors may increase the HF risk . Haque et al .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that aromatase inhibitors may increase the HF risk . Haque et al . studied CVD outcomes in over 13 000 post‐menopausal BC patients and found a higher HF risk in patients treated with aromatase inhibitors compared to patients treated with tamoxifen only (hazard ratios 1.1–1.3).…”
Section: Discussionmentioning
confidence: 99%
“…The largest datasets come from pediatric cancer survivors who are well followed after their cancer diagnoses and who seem to have increased rates of coronary artery disease. Also, the breast and prostate cancer patients, who are treated with hormone deprivation therapies for many years, appear to have slightly higher rates of coronary artery disease than the general population [6][7][8]. Finally, patients treated with other cancer therapies may experience increased rates of late coronary artery disease due to other factors such as increased systemic inflammation either due to the underlying disease, the treatments, the stress of treatment, or perhaps even due to changes in the microbiome that accompany a cancer diagnosis and treatment.…”
Section: Mechanisms and Types Of Cardiac Toxicitiesmentioning
confidence: 99%